The power of light from a non-phototrophic perspective: a phyllosphere dilemma - Alsanius, Beatrix W.; Hellström, Maria; Bergstrand, Karl-Johan; Vetukuri, Ramesh; Becher, Paul; Karlsson, Maria E. (Frontiers in Photobiology, 2024)
Plants and crop stands are considered holobionts, colonized by both autotrophic and by non-phototrophic heterotrophic microbiota. The dilemma in the exisiting body of studies is that the focus is primarily directed towards environmental specificties relevant for phototrophic organisms (predominantly plants), but does not take into account non-phototrophs. By definition, non-phototrophic heterotrophic bacteria do not use light as an energy source. Light energy and wavelength are rather used as a signal that can provoke shifts in both their metabolism and microbial lifestyle. Reaction and recovery time can vary between organisms and is dependent on the organism’s physiological stage. The length of the lighting event affects the energy an organism is exposed to. We argue that to obtain a deeper and more distinct understanding of light exposure (irradiance, exposure length), quantity (light intensity), and quality (wavelength/spectral distribution, bandwidth at full-width half-maximum) related mechanisms on non-phototrophic bacteria in the phyllosphere, the light environment needs to be further strictly characterized. This includes information on the actual energy hitting planktonic or sessile non-phototrophic bacteria resident on and inside plants aboveground. Mapping the light environment in ecosystems aids in unraveling light-phyllosphere interactions and strengthens their transdisciplinary character. This issue is fundamental in order to revisit and repeat others’ experimental approaches and findings but also to be able to translate findings into further action.